Large herbivores facilitate an insect herbivore by modifying plant community composition in a temperate grassland. Issue 22 (9th November 2021) - Li, Xiaofei; Wang, Shengnan; Prather, Chelse; Wan, Ho Yi; Zhu, Hui; Nummi, Petri; Inbar, Moshe; Gao, Qiang; Wang, Deli; Zhong, Zhiwei
Abstract: Large herbivores often co‐occur and share plant resources with herbivorous insects in grassland ecosystems; yet, how they interact with each other remains poorly understood. We conducted a series of field experiments to investigate whether and how large domestic herbivores (sheep; Ovis aries ) may affect the abundance of a common herbivorous insect (aphid; Hyalopterus pruni ) in a temperate grassland of northeast China. Our exclosure experiment showed that 3 years (2010–2012) of sheep grazing had led to 86% higher aphid abundance compared with ungrazed sites. Mechanistically, this facilitative effect was driven by grazing altering the plant community, rather than by changes in food availability and predator abundance for aphids. Sheep significantly altered plant community by reducing the abundance of unpalatable forbs for the aphids. Our small‐scale forb removal experiment revealed an "associational plant defense" by forbs which protect the grass Phragmites australis from being attacked by the aphids. However, selective grazing on forbs by sheep indirectly disrupted such associational plant defense, making P . australis more susceptible to aphids, consequentially increasing the density of aphids. These findings provide a novel mechanistic explanation for the effects of large herbivores on herbivorous insects by linking selective grazing to plant community composition and the responses of insect populations in grassland ecosystems. Abstract : In a temperate grassland in northern China, we found that selective grazing of forbs by sheep indirectly disrupted associational plant defense between forbs and Phragmites australis, making this grass species more susceptible to Hyalopterus pruni aphids, and thus benefited aphid population abundance.